The fossil flora of Great Britain or, figures and descriptions of the vegetable remains found in fossil state in this country - Lindley, John 1799-1865 (Cambridge University Press, 2015)
Employed early on in his career by Sir Joseph Banks, the botanist John Lindley went on to conduct important research on the orchid family & also recommended that Kew Gardens should become a national botanical institution. This pioneering three-volume work of palaeobotany, first published between 1831 & 1837, catalogues almost 300 species of fossil plants from the Pleistocene to the Carboniferous period. The geologist & palaeontologist William Hutton, with whom Lindley collaborated, was responsible for collecting the fossil speciments from which the 230 plates were drawn. The first serious attempt at organising & interpreting the evidence of Britain's primeval plant life, this resource is notable also for its prefatory discussion of topics such as coal seams & prehistoric climate. Volume 2 opens with a preface on coal, followed by descriptions of some of the fossil plants found therein.